Using Wavelets to Understand the Relationship between Mortgages and Gross Domestic Product in Spain - C. González-Concepción; M. C. Gil-Fariña; C. Pestano-Gabino (Journal of Applied Mathematics)
We use wavelet multiresolution decomposition and cross-wavelet analysis to reveal certain properties in financial data related to mortgages to households and gross domestic product data in Spain. Wavelet techniques possess many desirable properties, some of which are useful as a vehicle for analysing economic and financial data. In our case, wavelets are useful for drawing conclusions both in the time and frequency domains and for obtaining information on the different phases through which the study variables progress.